Caracterização hidrodinâmica e morfo-sedimentar do estuário Potengi e áreas adjacentes: subsídios para controle e recuperação ambiental no caso de derrames de hidrocarboneto - Frazão, Eugênio Pires (2003)
This study presents the Environmental Sensibility Mapping to oil spillings on the Potengi estuary - RN and neighboring coastline through remote sensing data, collecting, treatment and integration of the geomorphologic, oceanographic (temperature, salinity, density, direction and intensity), meteorological (wind speed and direction) and high resolution seismic (bathymetry and sonography) data. The Potengi river estuary is located on the eastern coastline of the Rio Grande do Norte State, being inserted in the geological context for the coastal Pernambuco-Paraíba basin and spreading over 18 km; it shelters the Natal harbor zone and an oil terminal, centralizing, therefore, important oil transport operations that can cause accidental spillings. Under the oceanographic point of view, the Potengi estuary is characterized by the absence of any expressive thermic stratification, being classified as partially mixed, B type according to Pritchard (1955), and 2 type in conformity to the stratification-circulation diagram by Hansen & Rattray (1966). Two main wind systems are responsable for the formation of wave sets that occur in the area. The dynamic tide presents, in the Natal Harbor, mean amplitude in spring and quadrature tides, with around 2.8 and 2m, respectively. The mechanism of saline tide mixing was defined through the salinity which is the main parameter for the identification of this mechanism. Important variations of the salinity mean values (36.32 psu), temperature (28.11ºC) and density (22.96 kg/m3) in the estuarine waters presented features belonging to low latitude regions. The water temperature follows the air temperature variations, in the region, with expressive daily amplitudes. In this study, the identification of the estuarine bed morphology through bathymetric and sonographic analysis, had the purpose to evaluate the influence of the superficial and bottom currents for the bottom shaping. In this way, the use of the side scan sonar showed, to be very useful in the identification of the bottom morphology and its relationship with the predominant action of the tidal currents in the Potengi estuary. Besides, it showed how the sonograms can be a support to the comparison of the several patterns derived from the local hydrodynamic variations. The holocene sediments, which fill the estuarine channel, are predominantly sandy, varying from selected, sometimes silty. The sedimentation is controlled by the environmental hydrodynamic conditions, being recognized two important textural facies: Muddy Facies and Sandy Facies. The distribution of these textural facies apparently oscillates owing to the tidal cycle and flow intensity. Each one of the above mentioned data was integrated in a Geographic Information System (GIS), from which was produced the Environmental Sensibility Map to oil spillings with Coastal Sensibility Index (CSI) to the Potengi estuary. The integrated analysis of these data is essential to oil spilling contingency plans, in order to reduce the spilling environmental consequences and to make efficient the endeavours of contention and cleaning up/removal on the Natal Harbor. This study has the aim to collaborate for the increase of informations about the estuarine environment and contribute to a better management of the question: environment/polluting loads